Fluorine-doped composite micro / mesoporous carbon material preparation method based on collaborative pore forming
By using fluorine-doped composite micro/mesoporous carbon materials based on collaborative pore formation in sodium metal secondary batteries, the problems of short battery cycle life and poor cycle stability are solved, and a more uniform solid electrolyte interface generation and sodium metal are achieved. Deposition significantly improves the cycle stability and energy density of the battery.
Patent Information
- Application Number
- CN202411605757.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-14
AI Technical Summary
The existing ‘negative-free’ sodium metal secondary batteries have short cycle life and poor cycle stability during the cycle process, mainly due to the continuous formation and destruction of the unstable solid electrolyte interface (SEI), resulting in dendrite growth and sodium consumption.
Using the preparation method of fluorine-doped composite micro/mesoporous carbon material based on co-porous formation, the mesoporous pore-making agent and microporous pore-making agent are prepared, combined with polyacrylonitrile for electrospinning, and in an inert argon atmosphere. The pyrolysis is formed to form a fluorine-doped carbon fiber material with a microporous covering mesoporous structure. This material can produce SEI evenly, inhibiting the excessive decomposition of the electrolyte on the electrode surface.
By forming uniform SEI and constraining sodium metal dense deposition, the cycle stability and energy density of sodium metal secondary batteries are significantly improved, the cycle life of the battery is extended, and the efficiency of Coulomb is improved.
Smart Images

Figure CN119433760A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage devices, and in particular to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on coordinated pore formation. Background Art
[0002] Sodium-based batteries are one of the ideal choices for building large-scale energy storage systems due to their abundant raw material reserves and similar electrochemical principles to lithium-based batteries, which will help achieve sustainable energy development. However, sodium-ion batteries using hard carbon anodes cannot meet the needs of secondary batteries for high energy density because their storage capacity is limited by the structure of the hard carbon itself. In contrast, sodium metal has significant advantages in building high energy density secondary batteries due to its high theoretical specific capacity and low electrochemical potential. However, the severe volume changes on the negative electrode side of sodium metal secondary batteries during the cycle, dendrite growth, and excessive use of sodium hinder the application of metallic sodium anodes and limit the further improvement of energy density.
[0003] For sodium metal batteries under practical conditions, stable cycling under low N / P (negative electrode to positive electrode capacity ratio less than 2) and high DOD (negative electrode discharge depth greater than 90%) conditions is a necessary condition for achieving high energy density sodium metal secondary batteries. In response to this, "negative electrode-free" sodium metal secondary batteries have been proposed to further improve the energy density of sodium-based batteries. "Negative electrode-free" sodium metal secondary batteries use a bare current collector without sodium metal as the negative electrode, and all sodium comes directly from the positive electrode. Compared with current sodium-based batteries, "negative electrode-free" sodium metal secondary batteries have the following advantages: (i) increased volumetric and gravimetric energy density, (ii) reduced use of metallic sodium to improve battery safety and economic benefits, and (iii) simplified manufacturing and assembly processes. However, under the condition of limited sodium metal, the cycling stability of "negative electrode-free" sodium metal secondary batteries drops sharply due to the continuous formation and destruction of the unstable solid electrolyte interface (SEI), resulting in dendrite growth and continuous sodium consumption. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the present invention provides a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on coordinated pore formation, so as to form a uniform solid electrolyte interface and inhibit excessive decomposition of the electrolyte on the electrode surface.
[0005] The present invention provides a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore formation, comprising the following steps: preparing a mesoporous pore former, ultrasonically dispersing the mesoporous pore former in N,N-dimethylformamide (DMF), adding the microporous pore former and stirring to obtain a first dispersion, adding polyacrylonitrile (PAN) to the first dispersion and stirring evenly to obtain a second dispersion, electrostatically spinning the second dispersion to obtain a spinning sample, and pyrolyzing the spinning sample to obtain a fluorine-doped composite micro / mesoporous carbon material.
[0006] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore formation provided by the present invention, the mesoporous pore former includes a nano-metal organic framework material (MOF material); the microporous pore former includes a perfluorinated polymer material.
[0007] According to a method for preparing fluorine-doped composite micro / mesoporous carbon materials based on synergistic pore formation provided by the present invention, the fluorine-doped composite micro / mesoporous carbon material includes a carbon fiber base material and fluorine elements uniformly doped in the carbon fiber base material, and the fluorine elements in the perfluorinated polymer material are in-situ doped into the carbon fiber base material during the pyrolysis of the spinning sample.
[0008] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore formation provided by the present invention, the preparation of a mesoporous pore former includes the following steps: dissolving a zinc salt in a mixed solvent consisting of N,N-dimethylformamide, ethanol, deionized water and ammonia water to obtain a first mixed solution, mixing 1,2,3-triazole and a polyether (F-127) surfactant to obtain a second mixed solution, mixing the first mixed solution and the second mixed solution to obtain a first precipitate, washing and drying the first precipitate to obtain a mesoporous pore former.
[0009] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on cooperative pore formation provided by the present invention, the zinc salt includes one or more of zinc chloride, zinc acetate, zinc nitrate and zinc sulfate; The mass range of the zinc salt is 1g~4g; The N,N-dimethylformamide adopts a 98% by mass N,N-dimethylformamide solution, and the volume range of the N,N-dimethylformamide solution is 10mL to 40mL; The ethanol is an ethanol solution with a mass fraction of 99.5%, and the volume range of the ethanol solution is 10 mL to 40 mL; The volume range of the deionized water is 10 mL to 50 mL; The ammonia water has a mass fraction of 98%, and the volume range of the ammonia water is 1 mL to 20 mL; The 1,2,3-triazole adopts a 1,2,3-triazole solution with a mass fraction of 98%, and the volume range of the 1,2,3-triazole is 0.5mL~5mL; The mass range of the polyether surfactant is 0.1g~2g.
[0010] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore-forming provided by the present invention, the mass range of the mesoporous pore-forming agent is 0.4 g to 1 g.
[0011] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore-forming provided by the present invention, the mass range of the microporous pore-forming agent is 0.1 g to 1 g.
[0012] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on cooperative pore formation provided by the present invention, the mass range of the polyacrylonitrile is 0.4g~1g; The N,N-dimethylformamide adopts a 98% by mass N,N-dimethylformamide solution, and the volume range of the N,N-dimethylformamide solution is 2 mL to 10 mL.
[0013] According to a method for preparing fluorine-doped composite micro / mesoporous carbon materials based on collaborative pore formation provided by the present invention, the electrospinning conditions include a temperature range of 15°C to 45°C, an ambient humidity range of 15%RH to 45%RH, an injection speed range of 8uL / min to 20uL / min, an injection distance range of 8cm to 30cm, and a needle model range of 16 to 24.
[0014] According to a method for preparing fluorine-doped composite micro / mesoporous carbon materials based on synergistic pore formation provided by the present invention, the temperature range for pyrolysis of the spinning sample is 500° C. to 1000° C.; the pyrolysis time is 1 h to 6 h.
[0015] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects: According to the method for preparing fluorine-doped composite micro / mesoporous carbon materials based on synergistic pore formation in an embodiment of the present invention, a carbon fiber material with a special uniform pore structure in which micropores cover mesopores is formed by pyrolyzing the spinning sample, thereby solving the problems of short cycle life and poor cycle stability of existing "negative electrode-free" sodium metal secondary batteries, and achieving internal mesopores that can constrain the dense deposition of sodium metal, and external micropores that can promote the formation of a uniform solid electrolyte interface, thereby inhibiting excessive decomposition of the electrolyte on the electrode surface.
[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] FIG1( a ) is a SEM image of the white powder MET-6 obtained in Example 1 provided by the present invention with a scale of 400 nm.
[0019] FIG1( b ) is a SEM image of the white powder MET-6 obtained in Example 1 provided by the present invention with a scale of 100 nm.
[0020] FIG2 (a) is a SEM image of the calcined FMCNF sample obtained in Example 2 provided by the present invention with a scale of 100 nm.
[0021] FIG2( b ) is a SEM image of the calcined FMCNF sample obtained in Example 2 provided by the present invention with a scale of 20 nm.
[0022] Figure 3 This is the X-ray diffraction pattern of the calcined sample FMCNF obtained in Example 2 provided by the present invention.
[0023] Figure 4 This is the pore size distribution diagram of the calcined sample FMCNF obtained in Example 2 provided by the present invention.
[0024] Figure 5 This is a SEM image of the calcined MCNF sample obtained in Comparative Example 1 provided by the present invention with a scale of 100 nm.
[0025] Figure 6 This is the pore size distribution diagram of the calcined sample MCNF obtained in Comparative Example 1 provided by the present invention.
[0026] Figure 7 It is the voltage curve of the batteries Na||FMCNF, Na||MCNF and Na||Cu during the first cycle discharge deposition process in Example 3 and Comparative Example 2 provided by the present invention.
[0027] Figure 8 It is the cycle coulombic efficiency (Coulombic efficiency) of the batteries Na||FMCNF, Na||MCNF and Na||Cu in Example 3 and Comparative Example 2 provided by the present invention.
[0028] FIG9( a ) is an optical photograph of the FMCNF produced in Example 2 provided by the present invention.
[0029] FIG9( b ) is an optical photograph of the composite sodium metal negative electrode Na-FMCNF prepared in Example 4 provided by the present invention.
[0030] Fig.10 The embodiment 5 and the comparative example 4 provided by the present invention are at 1 mA / cm 2 , 3mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 The relationship between the voltage and time of the symmetrical battery packs Na-Cu||Na-Cu, Na-MCNF||Na-MCNF and Na-FMCNF||Na-FMCNF at the current density.
[0031] Fig.11 This is the relationship between the voltage of the symmetrical battery Na-FMCNF||Na-FMCNF and time during the cycle process of Example 5 provided by the present invention.
[0032] Fig.12 This is the relationship between the voltage of the symmetrical battery Na-MCNF||Na-MCNF and time during the cycle process of the symmetrical battery Na-MCNF||Na-MCNF of comparative example 4 provided by the present invention.
[0033] FIG. 13 ( a ) shows the relationship between the first cycle voltage and the specific capacity of the battery of Example 6 provided by the present invention at a current of 0.1C.
[0034] FIG13( b ) shows the relationship between the first cycle voltage and the specific capacity of the battery of Comparative Example 5 provided by the present invention at a current of 0.1C.
[0035] Fig.14 It is the retention rate of the specific capacity of the batteries of Example 6 and Comparative Example 5 provided by the present invention after 200 cycles. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.
[0037] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0038] The present invention provides a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore formation, comprising the following steps: preparing a mesoporous pore former, ultrasonically dispersing the mesoporous pore former in N,N-dimethylformamide, adding the microporous pore former and stirring to obtain a first dispersion, adding polyacrylonitrile to the first dispersion and stirring evenly to obtain a second dispersion, electrostatically spinning the second dispersion to obtain a spinning sample, and pyrolyzing the spinning sample to obtain a fluorine-doped composite micro / mesoporous carbon material.
[0039] In this embodiment, the spun sample is pyrolyzed to form a carbon fiber material with a special uniform pore structure in which micropores cover mesopores, thereby solving the problems of short cycle life and poor cycle stability of existing "negative electrode-free" sodium metal secondary batteries. The internal mesopores constrain the dense deposition of sodium metal, and the external micropores promote the formation of a uniform solid electrolyte interface, thereby inhibiting excessive decomposition of the electrolyte on the electrode surface.
[0040] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on coordinated pore formation provided by the present invention, the mesoporous pore former includes a nano-metal organic framework material; the microporous pore former includes a perfluorinated polymer material.
[0041] According to a method for preparing fluorine-doped composite micro / mesoporous carbon materials based on synergistic pore formation provided by the present invention, the fluorine-doped composite micro / mesoporous carbon material includes a carbon fiber base material and fluorine elements uniformly doped in the carbon fiber base material, and the fluorine elements in the perfluorinated polymer material are in-situ doped into the carbon fiber base material during the pyrolysis of the spinning sample.
[0042] According to some preferred embodiments of the present invention, MOF material is ultrasonically dispersed in a DMF (N,N-dimethylformamide) solution, a perfluoropolymer material is added and stirred to obtain a first dispersion, polyacrylonitrile is added to the first dispersion and stirred evenly to obtain a second dispersion, the second dispersion is electrospun to obtain a spinning sample, and the spinning sample is pyrolyzed in an inert argon atmosphere. During the pyrolysis process, the perfluoropolymer material is preferentially decomposed at a lower temperature to form a microporous structure covering the MOF material, and then the pore-forming effect of the violent decomposition and gas production of the MOF material when the temperature rises is suppressed by the microporous structure on the surface, forming a mesoporous structure of uniform size, and finally a carbon fiber base material with a special uniform pore structure of micropores covering mesopores is obtained, and the fluorine element in the perfluoropolymer material is uniformly doped into the carbon fiber base material to obtain a fluorine-doped composite micro / mesoporous carbon material.
[0043] According to some embodiments of the present invention, the polyacrylonitrile is carbonized at high temperature during pyrolysis to provide a carbon fiber material.
[0044] According to some preferred embodiments of the present invention, the perfluorinated polymer material is polytetrafluoroethylene (PTFE).
[0045] According to some embodiments of the present invention, the pore size of the micropores is less than 2 nm, and the pore size of the mesopores is between 2-50 nm.
[0046] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore formation provided by the present invention, the preparation of a mesoporous pore former includes the following steps: dissolving a zinc salt in a mixed solvent consisting of N,N-dimethylformamide, ethanol, deionized water and ammonia water to obtain a first mixed solution, mixing 1,2,3-triazole with a polyether surfactant to obtain a second mixed solution, mixing the first mixed solution and the second mixed solution with stirring to obtain a first precipitate, washing and drying the first precipitate to obtain a mesoporous pore former.
[0047] According to some preferred embodiments of the present invention, washing and drying the first precipitate includes the following steps: washing the first precipitate once with DMF and then washing it once with ethanol, and then drying the first precipitate at 100° C. for 24 hours to obtain a MOF material.
[0048] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on cooperative pore formation provided by the present invention, the zinc salt includes one or more of zinc chloride, zinc acetate, zinc nitrate and zinc sulfate; The mass range of the zinc salt is 1g~4g; The N,N-dimethylformamide adopts a 98% by mass N,N-dimethylformamide solution, and the volume range of the N,N-dimethylformamide solution is 10mL to 40mL; The ethanol is an ethanol solution with a mass fraction of 99.5%, and the volume range of the ethanol solution is 10 mL to 40 mL; The volume range of the deionized water is 10 mL to 50 mL; The ammonia water has a mass fraction of 98%, and the volume range of the ammonia water is 1 mL to 20 mL; The 1,2,3-triazole adopts a 1,2,3-triazole solution with a mass fraction of 98%, and the volume range of the 1,2,3-triazole is 0.5mL~5mL; The mass range of the polyether surfactant is 0.1g~2g.
[0049] According to some preferred embodiments of the present invention, the mass range of the zinc salt is 1.5g~3g.
[0050] According to some preferred embodiments of the present invention, the volume of the N,N-dimethylformamide solution ranges from 15 mL to 30 mL.
[0051] According to some preferred embodiments of the present invention, the volume range of the ethanol solution is 15 mL to 30 mL.
[0052] According to some preferred embodiments of the present invention, the volume range of the deionized water is 20 mL to 40 mL.
[0053] According to some preferred embodiments of the present invention, the volume range of the ammonia water is 5 mL to 15 mL.
[0054] The 1,2,3-triazole adopts a 1,2,3-triazole solution with a mass fraction of 98%, and the volume range of the 1,2,3-triazole is 1 mL to 3 mL.
[0055] The mass range of the polyether surfactant is 0.5g~1.5g.
[0056] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore-forming provided by the present invention, the mass range of the mesoporous pore-forming agent is 0.4 g to 1 g.
[0057] According to some preferred embodiments of the present invention, the mass range of the mesoporous pore former is 0.6 g to 0.8 g.
[0058] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on synergistic pore-forming provided by the present invention, the mass range of the microporous pore-forming agent is 0.1 g to 1 g.
[0059] According to some preferred embodiments of the present invention, the mass range of the microporous pore former is 0.2g~0.4g.
[0060] According to a method for preparing a fluorine-doped composite micro / mesoporous carbon material based on cooperative pore formation provided by the present invention, the mass range of the polyacrylonitrile is 0.4g~1g; The N,N-dimethylformamide adopts a 98% by mass N,N-dimethylformamide solution, and the volume range of the N,N-dimethylformamide solution is 2 mL to 10 mL.
[0061] According to some preferred embodiments of the present invention, the mass range of the polyacrylonitrile is 0.5g~0.8g.
[0062] According to a method for preparing fluorine-doped composite micro / mesoporous carbon materials based on collaborative pore formation provided by the present invention, the electrospinning conditions include a temperature range of 15°C to 45°C, an ambient humidity range of 15%RH to 45%RH, an injection speed range of 8uL / min to 20uL / min, an injection distance range of 8cm to 30cm, and a needle model range of 16 to 24.
[0063] According to some preferred embodiments of the present invention, the electrospinning conditions include a temperature range of 20°C~30°C, an ambient humidity range of 20%RH~35%RH, an injection speed range of 10uL / min~15uL / min, an injection distance range of 12cm~25cm, and a needle model range of 18~21.
[0064] According to a method for preparing fluorine-doped composite micro / mesoporous carbon materials based on synergistic pore formation provided by the present invention, the temperature range for pyrolysis of the spinning sample is 500° C. to 1000° C.; the pyrolysis time is 1 h to 6 h.
[0065] According to some preferred embodiments of the present invention, the temperature range of pyrolysis is 600° C. to 800° C.; and the time of pyrolysis is 2 h to 4 h.
[0066] According to some preferred embodiments of the present invention, a composite sodium metal negative electrode is prepared by using a fluorine-doped composite micro / mesoporous carbon material prepared by a fluorine-doped composite micro / mesoporous carbon material preparation method based on synergistic pore formation, and the preparation method comprises the following steps: in a glove box with a water oxygen value lower than 0.1 ppm, heating a sodium metal block until the sodium metal block has a certain fluidity, contacting the fluorine-doped composite micro / mesoporous carbon material with a sodium metal melt, to prepare a composite sodium metal negative electrode.
[0067] According to some embodiments of the present invention, the heating temperature range of the sodium metal block is 150°C to 300°C; preferably, the heating temperature range is 160°C to 200°C.
[0068] According to some embodiments of the present invention, the fluorine-doped composite micro / mesoporous carbon material is directly cut into a negative electrode side current collector for a "negative electrode-free" sodium metal secondary battery and applied to a "negative electrode-free" sodium metal secondary battery.
[0069] The technical solution of the present invention is further explained below in conjunction with a specific embodiment. It should be noted that this specific embodiment is only for those skilled in the art to better understand the technical solution of the present invention, and should not be regarded as an unreasonable limitation on the protection scope of the present invention.
[0070] Example 1 FIG. 1( a ) is a SEM image of the white powder MET-6 obtained in Example 1 provided by the present invention with a scale of 400 nm, and FIG. 1( b ) is a SEM image of the white powder MET-6 obtained in Example 1 provided by the present invention with a scale of 100 nm.
[0071] 2g of anhydrous zinc chloride was dissolved in a mixed solvent consisting of 20mL of N,N-dimethylformamide (DMF), 20mL of ethanol, 30mL of deionized water and 10mL of ammonia water to form a first mixed solution. 2.5mL of 1,2,3-triazole was mixed with 1.2g of a polyether surfactant to obtain a second mixed solution. The first mixed solution was added to the second mixed solution and stirred continuously at room temperature for 2 hours. The obtained white precipitate was washed once with DMF and once with ethanol, and then dried at 100°C for 24 hours to obtain a white powder. The obtained white powder was designated as MET-6, and its SEM morphology is shown in Figures 1 (a) and 1 (b).
[0072] Example 2 Figure 2 (a) is a SEM image of the calcined sample FMCNF obtained in Example 2 provided by the present invention with a scale of 100 nm. Figure 2 (b) is a SEM image of the calcined sample FMCNF obtained in Example 2 provided by the present invention with a scale of 20 nm. Figure 3 This is the X-ray diffraction pattern of the calcined sample FMCNF obtained in Example 2 provided by the present invention. Figure 4 This is the pore size distribution diagram of the calcined sample FMCNF obtained in Example 2 provided by the present invention.
[0073] 0.65g of MET-6 was ultrasonically dispersed in 5mL of DMF, and then 0.1g of polytetrafluoroethylene was added and stirred to obtain the first dispersion. Polyacrylonitrile was added to the first dispersion and stirred to dissolve to obtain the second dispersion. The second dispersion was electrospun, wherein the injection speed of electrospinning was 15uL / min, the needle was No. 21, the distance between the needle and the plate was 18cm, the ambient humidity was 25%RH, and the temperature was 25°C. The obtained spinning sample was dried at 70°C for 24 hours, and then placed in an argon tube furnace for calcination, the calcination temperature was 800°C, and the heating rate for calcination for 2 hours was 5°C / min. The obtained calcined sample was recorded as FMCNF. The SEM morphology of FMCNF is shown in Figure 2 (a) and Figure 2 (b). In Figure 2 (a), it can be seen that the fiber surface is smooth. In Figure 2 (b), after magnifying Figure 2 (a) 5 times, it can be clearly seen that FMCNF has a unique structure of micropores covering mesopores, and the fiber surface is smooth. The X-ray diffraction pattern (XRD) of FMCNF is shown in Figure 3 As shown, from Figure 3 It can be seen from the XRD diagram that there is no obvious mutation in the spectrum, and the FMCNF sample is in an amorphous state, indicating that there is no obvious crystalline product inside. Figure 4 There are mutations at the pore width of 1.2nm and 6nm, which shows that the pore size distribution of the material is mainly composed of micropores of 1.2nm and mesopores of about 6nm, further proving that FMCNF has a unique structure of micropores covering mesopores.
[0074] Comparative Example 1 Figure 5 This is a SEM image of the calcined MCNF sample obtained in Comparative Example 1 provided by the present invention with a scale of 100 nm. Figure 6 This is the pore size distribution diagram of the calcined sample MCNF obtained in Comparative Example 1 provided by the present invention.
[0075] Ultrasonic dispersion of 0.65 g of MET-6 was obtained in 5 mL of DMF to obtain a first dispersion. Polyacrylonitrile was added to the first dispersion and stirred to dissolve to obtain a second dispersion. The second dispersion was subjected to electrospinning, wherein the electrospinning injection speed was 15 uL / min, the needle was No. 21, the distance between the needle and the plate was 18 cm, the ambient humidity was 25% RH, and the temperature was 25°C. The obtained spinning sample was dried at 70°C for 24 hours, and then placed in an argon tube furnace for calcination at a calcination temperature of 800°C, and the heating rate for calcination for 2 hours was 5°C / min. The obtained calcined sample was recorded as MCNF. The SEM morphology of MCNF is shown in Figure 5 As shown, from Figure 5 It can be seen that MCNF is mainly distributed with uneven large mesopores, which makes the fiber surface of MCNF relatively rough and irregular. Figure 6The middle line floats between pore diameters of 5 and 35 nm, further indicating that the pore distribution of MCNF is composed of large mesopores of about 5 to 35 nm, and there is no microporous structure.
[0076] Example 3 Figure 7 It is the voltage curve of the batteries Na||FMCNF, Na||MCNF and Na||Cu during the first cycle discharge deposition process in Example 3 and Comparative Example 2 provided by the present invention. Figure 8 It is the cycle coulombic efficiency of the batteries Na||FMCNF, Na||MCNF and Na||Cu in Example 3 and Comparative Example 2 provided by the present invention.
[0077] The FMCNF slices obtained in Example 2 were cut into 10 mm diameter discs as electrode sheet A1, and copper foil slices were used as control electrode sheet B1. The assembled battery was tested for charge and discharge efficiency cycles. The sodium metal sheet was used as the negative electrode, the electrolyte was a mixed solution of 1 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether, the glass fiber was used as the diaphragm, and the CR2032 stainless steel was used as the battery shell. The battery made using electrode sheet A1 was recorded as Na||FMCNF, and the battery made using electrode sheet B1 was recorded as Na||Cu. The batteries Na||FMCNF and Na||Cu were charged at 1 mA / cm 2 The battery was discharged at a current density of 1000V for 1 hour, and then charged to 0.1V at the same current density, and then the discharge and charge process was repeated for a cycle. The coulombic efficiency of the battery Na||FMCNF and Na||Cu was calculated by statistically analyzing the ratio of the charge cut-off capacity to the discharge capacity. Figure 7 As shown in the figure, the change in the curve mutation of FMCNF is much smaller than that of copper foil, which indicates that FMCNF has a smaller nucleation overpotential of only 7mV, while the nucleation overpotential of copper foil is as high as 22mV, which reflects the sodium affinity of FMCNF. Figure 8 As shown, Na||FMCNF can cycle more than 2000 times at an average Coulombic efficiency of 99.88%, while Na||Cu can only cycle 320 times at an average Coulombic efficiency of 99.88%. The cycle number of Na||FMCNF is more than 5 times that of Na||Cu, and Na||FMCNF exhibits superior cycling stability.
[0078] Comparative Example 2 The MCNF slices obtained in comparative example 1 were cut into 10 mm diameter discs as electrode sheet C1, and the copper foil slices were used as control electrode sheet B1. The assembled batteries were tested for charge and discharge efficiency cycles. The sodium metal sheet was used as the negative electrode, the electrolyte was a mixed solution of 1 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether, the glass fiber was used as the diaphragm, and the CR2032 stainless steel was used as the battery shell. The battery made using electrode sheet C1 was recorded as Na||MCNF, and the battery made using electrode sheet B1 was recorded as Na||Cu. The batteries Na||MCNF and Na||Cu were charged at 1 mA / cm 2 The battery was discharged at a current density of 10000V for 1 hour, and then charged to 0.1V at the same current density. The discharge and charge process was repeated for a cycle. The coulombic efficiency of the battery Na||MCNF and Na||Cu was calculated by calculating the ratio of the charge cut-off capacity to the discharge capacity. Figure 7 As shown in the figure, the change in the curve corresponding to MCNF is slightly greater than that of FMCNF. The nucleation overpotential of MCNF is 10mV, which is higher than that of FMCNF, showing a poorer sodium affinity than FMCNF. Figure 8 As shown, Na||MCNF can cycle only 600 times at an average Coulomb efficiency of 99.88%. It can be seen that the cycle life of Na||MCNF is much lower than that of Na||FMCNF, indicating that fluorine doping in microporous-coated mesoporous carbon fiber materials is beneficial to improving the reversibility of sodium metal deposition / stripping.
[0079] Example 4 Figure 9 (a) is an optical photograph of the FMCNF prepared in Example 2 provided by the present invention. Figure 9 (b) is an optical photograph of the composite sodium metal negative electrode Na-FMCNF prepared in Example 4 provided by the present invention.
[0080] The FMCNF obtained in Example 2 was cut into a size of 4 cm*6 cm, as shown in FIG9 (a), and the edge was immersed in molten sodium metal at 200°C for sodium melt adsorption to prepare a composite sodium metal negative electrode Na-FMCNF, as shown in FIG9 (b). The obtained Na-FMCNF was sliced into 10 mm diameter discs as electrode sheets A2.
[0081] Example 5 Fig.10 The embodiment 5 and the comparative example 4 provided by the present invention are at 1 mA / cm 2 , 3mA / cm 2 , 5mA / cm 2 , 10mA / cm 2The relationship between the voltage and time of the symmetrical battery packs Na-Cu||Na-Cu, Na-MCNF||Na-MCNF and Na-FMCNF||Na-FMCNF at the current density. Fig.11 This is the relationship between the voltage of the symmetrical battery Na-FMCNF||Na-FMCNF and time during the cycle process of Example 5 provided by the present invention.
[0082] The electrode sheet A2 obtained in Example 4 was used as an electrode to assemble a symmetrical cell Na-FMCNF||Na-FMCNF, the electrolyte was a mixed solution of 1 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether, and glass fiber was used as a separator. As a control, a symmetrical cell Na||Na was assembled using sodium sheet B2. The obtained battery was subjected to rate performance testing. Fig.10 As shown, at 1mA / cm 2 , 3mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 At a current density of 10 mA / cm, the voltage fluctuation of Na-FMCNF||Na-FMCNF is relatively small, and both show a smaller overpotential, indicating that electrode A2 has better reaction kinetics. 2 , constant capacity 10mAh / cm 2 The next (discharge depth is 94%) cycle, such as Fig.11 As shown in Figure 5, the Na-FMCNF electrode can still stably cycle for more than 2000 h at a higher depth of discharge (DOD), indicating that electrode sheet A2 has a stable solid electrolyte interface.
[0083] Comparative Example 3 Na-MCNF was prepared by electrochemical deposition. The 10 mm diameter disc electrode C1 prepared in Comparative Example 2 was used to assemble a battery for electrochemical deposition of sodium metal. The sodium metal sheet was used as the negative electrode, the electrolyte was a mixed solution of 1 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether, the glass fiber was used as the diaphragm, and the CR2032 stainless steel was used as the battery shell. The surface loading of sodium metal deposited on the electrode sheet C1 was the same as that of the electrode sheet A2 prepared in Example 4, both of which were 11.6 mAh / cm 2 , i.e. 1.16 mA / cm 2 After discharging for 10 h, the battery was disassembled in a glove box to obtain Na-MCNF as the electrode sheet C2.
[0084] Comparative Example 4 Fig.12This is the relationship between the voltage of the symmetrical battery Na-MCNF||Na-MCNF and time during the cycle process of the symmetrical battery Na-MCNF||Na-MCNF of comparative example 4 provided by the present invention.
[0085] The electrode sheet C2 obtained in comparative example 3 was used as an electrode to assemble a symmetrical cell Na-MCNF||Na-MCNF, the electrolyte was a mixed solution of 1 mol / L NaPF6 dissolved in diethylene glycol dimethyl ether, and glass fiber was used as a separator. The obtained battery was tested for rate performance. Fig.10 As shown, at 3mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 At current densities of 10 mA / cm 2 At a current density of 10 mA / cm, Na-MCNF||Na-MCNF showed a larger overpotential, indicating poor electrode reaction kinetics. 2 , constant capacity 10mAh / cm 2 The next (discharge depth is 94%) cycle, such as Fig.12 As shown in the figure, Na-MCNF||Na-MCNF short-circuits at the beginning of the cycle, indicating that Na-MCNF has poor cycle stability, proving that doping with fluorine can inhibit excessive decomposition of the electrolyte on the electrode surface.
[0086] Example 6 FIG. 13 ( a ) shows the relationship between the first cycle voltage and the specific capacity of the battery of Example 6 provided by the present invention at a current of 0.1C. Fig.14 It is the retention rate of the specific capacity of the batteries of Example 6 and Comparative Example 5 provided by the present invention after 200 cycles.
[0087] The electrode sheet A1 obtained in Example 3 was used as the current collector on the negative electrode side, and sodium vanadium phosphate (NVP) was used as the positive electrode to assemble a "negative electrode-free" soft-pack full battery. The electrolyte was 1 mol / L NaClO4 dissolved in a mixed solution of ethylene carbonate (EC), diethyl carbonate (DEC) and 5% by mass of fluoroethylene carbonate (FEC). The volume ratio of EC and DEC was 1:1. Glass fiber was used as a separator to obtain an A1 "negative electrode-free" soft-pack full battery. The obtained battery was subjected to a constant current long cycle test. As shown in Figure 13 (a), at a current of 0.1C, the difference between the two lines at the turning point was small, about 0.05V, proving that the A1 "negative electrode-free" soft-pack full battery has a lower irreversible capacity loss in the first cycle. Fig.14As shown, after 200 cycles at 0.3C, the specific capacity of the A1 "negative electrode-free" soft-pack full battery decreased slightly, and the capacity retention rate was as high as 90%, further demonstrating that FMCNF as an electrode has a stable solid electrolyte interface.
[0088] Comparative Example 5 FIG13( b ) shows the relationship between the first cycle voltage and the specific capacity of the battery of Comparative Example 5 provided by the present invention at a current of 0.1C.
[0089] The electrode sheet C1 obtained in comparative example 2 was used as the negative electrode side current collector, sodium vanadium phosphate (NVP) was used as the positive electrode to assemble a "negative electrode-free" soft-pack full battery, the electrolyte was 1 mol / L NaClO4 dissolved in a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) and 5% by mass of fluoroethylene carbonate (FEC), the volume ratio of EC and DEC was 1:1, and glass fiber was used as a separator to obtain the C1 "negative electrode-free" soft-pack full battery. The obtained battery was subjected to a constant current long cycle test. As shown in Figure 13 (b), at a current of 0.1C, the difference between the two lines at the turning point was about 0.2V, which is equivalent to four times that of the A1 "negative electrode-free" soft-pack full battery, proving that the C1 "negative electrode-free" soft-pack full battery has a higher irreversible capacity loss in the first cycle. Fig.14 Under 0.3C conditions, the capacity of the C1 "negative electrode-free" soft-pack full battery decays to 0 after about 100 cycles. This shows that the A1 electrode as a negative electrode current collector can significantly improve the cycle life of the "negative electrode-free" sodium metal secondary battery.
[0090] Compared with the prior art, the method for preparing fluorine-doped composite micro / mesoporous carbon materials based on coordinated pore formation in the embodiment of the present invention has the following technical effects: (1) The present invention selects a metal organic framework material with nitrogen-rich organic ligands as a mesoporous pore-forming agent and a perfluorinated polymer polytetrafluoroethylene as a microporous pore-forming agent, and combines them in an electrospun film of polyacrylonitrile, and pyrolyzes them in an inert argon atmosphere to obtain a fluorine-doped microporous-covered-mesoporous carbon fiber material. The material has a special microporous-covered-mesoporous pore structure, the internal mesopores can constrain the dense deposition of sodium metal, the external micropores can promote the uniform SEI formation, and the fluorine doping can effectively inhibit the excessive decomposition of the electrolyte on the electrode surface.
[0091] (2) The fluorine-doped microporous-capped mesoporous carbon fiber material provided by the present invention has a high sodium affinity, can significantly reduce the sodium metal nucleation barrier, and can quickly prepare a composite sodium metal negative electrode by simple melt adsorption of sodium metal.
[0092] (3) The fluorine-doped microporous covered mesoporous carbon fiber material provided by the present invention can significantly inhibit the irreversible capacity loss of active sodium metal. 2Under high current conditions, 5000 reversible deposition / stripping cycles can be achieved with a Coulombic efficiency of up to 99.93%. In addition, stable cycling for more than 2000 hours can be achieved at a high depth of discharge (DOD) of 94%.
[0093] (4) The fluorine-doped microporous-coated mesoporous carbon fiber material provided by the present invention can significantly improve the reversibility of sodium metal deposition / stripping. When used as a current collector in a "negative electrode-free" sodium metal secondary battery, it can significantly improve the battery's cycle life and capacity retention rate (200 cycles, 90% capacity retention rate).
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing fluorine-doped composite micro / mesoporous carbon materials based on synergistic pore formation, characterized in that: The following steps are involved: A mesoporous pore-forming agent is prepared, the mesoporous pore-forming agent is ultrasonically dispersed in N,N-dimethylformamide, a microporous pore-forming agent is added and stirred to obtain a first dispersion, polyacrylonitrile is added to the first dispersion and stirred evenly to obtain a second dispersion, the second dispersion is electrospun to obtain a spinning sample, and the spinning sample is pyrolyzed to obtain a fluorine-doped composite micro / mesoporous carbon material.
2. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 1, characterized in that: The mesoporous pore-forming agent comprises a nano-metal organic framework material; the microporous pore-forming agent comprises a perfluorinated polymer material.
3. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 2, characterized in that: The fluorine-doped composite micro / mesoporous carbon material comprises a carbon fiber base material and fluorine elements uniformly doped in the carbon fiber base material. During the pyrolysis of the spinning sample, the fluorine elements in the perfluoropolymer material are in-situ doped into the carbon fiber base material.
4. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 1, characterized in that: The preparation of a mesoporous pore-forming agent comprises the following steps: dissolving a zinc salt in a mixed solvent consisting of N,N-dimethylformamide, ethanol, deionized water and ammonia water to obtain a first mixed solution; mixing 1,2,3-triazole with a polyether surfactant to obtain a second mixed solution; mixing the first mixed solution with the second mixed solution and stirring to obtain a first precipitate; washing and drying the first precipitate to obtain a mesoporous pore-forming agent.
5. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 4, characterized in that: The zinc salt includes one or more of zinc chloride, zinc acetate, zinc nitrate and zinc sulfate; The mass range of the zinc salt is 1g~4g; The N,N-dimethylformamide adopts a 98% by mass N,N-dimethylformamide solution, and the volume range of the N,N-dimethylformamide solution is 10mL to 40mL; The ethanol is an ethanol solution with a mass fraction of 99.5%, and the volume range of the ethanol solution is 10 mL to 40 mL; The volume range of the deionized water is 10 mL to 50 mL; The ammonia water has a mass fraction of 98%, and the volume range of the ammonia water is 1 mL to 20 mL; The 1,2,3-triazole adopts a 1,2,3-triazole solution with a mass fraction of 98%, and the volume range of the 1,2,3-triazole is 0.5mL~5mL; The mass range of the polyether surfactant is 0.1g~2g.
6. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 1, characterized in that: The mass range of the mesoporous pore former is 0.4 g to 1 g.
7. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 1, characterized in that: The mass range of the microporous pore former is 0.1 g to 1 g.
8. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 1, characterized in that: The mass range of the polyacrylonitrile is 0.4g~1g; The N,N-dimethylformamide adopts a 98% by mass N,N-dimethylformamide solution, and the volume range of the N,N-dimethylformamide solution is 2 mL to 10 mL.
9. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 1, characterized in that: The electrospinning conditions include a temperature range of 15°C to 45°C, an ambient humidity range of 15%RH to 45%RH, an injection speed range of 8uL / min to 20uL / min, an injection distance range of 8cm to 30cm, and a needle model range of 16 to 24.
10. The method for preparing fluorine-doped composite micro / mesoporous carbon materials based on cooperative pore formation according to claim 1, characterized in that: The temperature range of pyrolysis of the spinning sample is 500° C. to 1000° C.; the pyrolysis time is 1 h to 6 h.